Development of a Self-Restricting CRISPR-Cas9 System to Reduce Off-Target Effects - Wang, Hui (Mol Ther Methods Clin Dev, 2020)
Development of the CRISPR-Cas9 gene-editing system has given rise to a new era of gene editing with wide applications in biology, medicine, agriculture, and other fields. However, the overexpression of Cas9 nuclease causes off-target effects and may trigger an immune response in vivo. Therefore, we constructed a self-restricting CRISPR-Cas9 system, where the target gene sequence corresponding to the guide RNA (gRNA) is inserted on either end of the Cas9 promoter. When double-strand breaks (DSBs) are induced in the target gene sequence, the Cas9 promoter is cut off and transcription ceases. With this system, expression of Cas9 protein at 60 h after transfection is only 10% that of the wild-type system, with about 70% promoter deletion efficiency. The target site editing efficiency and homologous recombination efficiency of the self-restricting system remain at about 50% and 30%, respectively, while the frequency of off-target indel formation decreased by 76.7%. Further, the number of indel types was also reduced from 13 to 2. Because this system does not include additional gRNA sequences, the possibility of introducing new off-target mutations is decreased. Importantly, this system is composed of a single plasmid, which could potentially be easily introduced in vivo using a viral vector or nanoparticles.